An Experimental Investigation into the Enhancement of Surface Quality of Inconel 718 Through Axial Ultrasonic Vibration-Assisted Grinding in Dry and MQL Environments - Sreethul Das; Pandivelan Chinnaiyan; Joel Jayaseelan; Jeyapandiarajan Paulchamy; Andre Batako; Ashwath Pazhani (Journal of Manufacturing and Materials Processing, 2024)
Ultrasonic vibration-assisted grinding (UVAG) has proven to be beneficial for grinding difficult-to-machine materials. This work attempts to enhance the grinding performance of Inconel 718 through a comprehensive study of UVAG characteristics. Grinding experiments were performed in both dry and Minimum Quantity Lubrication (MQL) environments, and assessment of the grinding forces, specific energy, residual stress, and surface topography was done. A substantial reduction of both surface roughness and grinding force components was observed in UVAG compared to conventional grinding (CG). Utilizing UVAG with MQL at the maximum vibration amplitude led to a 64% reduction in tangential grinding force and a 51% decrease in roughness parameter, Ra, when compared to CG conducted in a dry environment. The high-frequency indentations of the abrasives in UVAG generated compressive residual stresses on the ground surface. Surface parameters pointed to uniform texture and SEM images showed widening of abrasive grain tracks on the workpiece surface during UVAG. The utilization of UVAG under MQL produced a synergistic impact and resulted in the lowest grinding forces, specific energy, and optimal surface quality among all the grinding conditions investigated. Overall analysis of the results indicated that the axial configuration of the vibration set-up is favorable for UVAG, and the high-frequency periodic separation-cutting characteristic of the process improves lubricating efficiency and grinding performance.